Linking Nitrogen Losses With Crop Productivity in Maize Agroecosystems - Greer, Kristin D.; Pittelkow, Cameron M. (Frontiers in Sustainable Food Systems, 2018)
To meet sustainable intensification goals in the US Midwest, strategies which maintain or increase yields while minimizing negative impacts on water quality are needed. In this study maize yield response and potential nitrogen (N) leaching losses were simultaneously quantified to test the hypothesis that N rates which produced maximum yields would result in minimum yield-scaled N leaching potential. Field experiments were conducted at two sites in 2015 and 2016 to determine the effect of N rate (0, 79, 179, 269 kg N ha-1) on yield, crop N uptake, potential N leaching losses, and post-harvest soil N concentrations. Results show that a significant yield response (up to 179 kg N ha-1) occurred in all years compared to the control. Nitrogen leaching potential increased at 269 kg N ha-1 compared to the control in 2015 but not 2016. Yield-scaled N leaching potential was not statistically different among treatments in three of four site-years. There was no improvement in crop N uptake or N recovery efficiency for 269 kg N ha-1 compared to 179 kg N ha-1 in three of four site-years, which coincided with a trend of increasing post-harvest soil N concentrations, further escalating the risk of environmental N losses. These results did not support our hypothesis that yield-scaled N leaching potential is minimized at N rates that optimize yields (on a normalized basis yield-scaled N leaching potential increased by 28% compared to the control). However, normalized data indicate that 179 kg N ha-1, the N rate most closely aligned with current recommendations in this region, resulted in 96% of maximum yield while preventing a 25% increase in yield-scaled N leaching potential compared to 269 kg N ha-1, underscoring the potential for achieving high yields while avoiding increased N leaching potential on an environmental efficiency basis.